The Meaning of the Principle of Material Legality in Reforming Indonesian Criminal Law - Ismawati Septiningsih; Sri Wahyuningsih Yulianti (ARIMA : Jurnal Sosial Dan Humaniora, 2023)
The principle of legality is a very important principle in criminal law. The principle of legality plays an important role in the implementation of material criminal law rules and is the basis for the legitimacy of actions that are categorized as criminal acts. Criminal law reform with the ratification of Law Number 1 of 2023 concerning the Criminal Code does not only change the sound of the formulation of the principle of legality in a substantial way, but also changes the principle of formal legality, which was previously far from society's sense of justice, to be expanded into a principle of material legality that ensure a greater sense of justice in society. This article will discuss the principle of material legality as an update of the principle of formal legality which aims to expand the reach of the principle of legality in providing protection for society from the negative consequences resulting from criminal acts.